Analisis Yuridis Penegakan Hukum atas Pelanggaran Izin dalam Undang-Undang No. 32 Tahun 2009 - Nazah, Farida Nurun; Renanta, Yunesia Amelia; Ramadan, Aesa Rizki; Arkananta, Rakha Purwa; Anggraini, Naswa Fiolla; Agustina, Winda; Wijaya, Friska Nova; Sahputra, Dedi; Salsabil, Aida Hanan Putri (Universitas Muhammadiyah Ponorogo, 2025)
Environmental licensing violations have become a significant factor accelerating ecosystem degradation in Indonesia. Licensing instruments, which are supposed to function as preventive and controlling tools, are often neglected by both business actors and local governments. This research aims to analyze law enforcement against environmental licensing violations based on Law Number 32 of 2009 concerning Environmental Protection and Management, while also examining its effectiveness, challenges, and potential improvements. This study employs a normative juridical research type with a statutory and case study approach. The data consist of primary, secondary, and tertiary legal materials obtained through literature review and documentation. Data analysis was carried out qualitatively by interpreting applicable legal norms and comparing them with law enforcement practices in the field. Data validity was ensured through source triangulation, combining statutory provisions, legal doctrines, and empirical findings from relevant case studies. The findings reveal that licensing violations generally include neglect of Environmental Impact Assessment (Amdal), environmental permits, and business activities conducted without UKL-UPL documents. Law enforcement measures cover administrative, criminal, and civil instruments, yet their implementation remains ineffective due to weak supervision, the lack of deterrent sanctions, and conflicts of interest among stakeholders. This study concludes that law enforcement on licensing violations has not been optimal and requires strengthening in regulatory frameworks, institutional capacity, and public participation. Strengthening inter-agency coordination, enforcing strict sanctions without discrimination, and encouraging community involvement are deemed essential to enhance compliance and improve environmental governance in Indonesia.